Family functioning in bipolar disorder: Characteristics, congruity between patients and relatives, and clinical correlates. (30th November 2016) - Reinares, María; Bonnín, C. Mar; Hidalgo-Mazzei, Diego; Colom, Francesc; Solé, Brisa; Jiménez, Esther; Torrent, Carla; Comes, Mercè; Martínez-Arán, Anabel; Sánchez-Moreno, José; Vieta, Eduard
Abstract: Functional improvement has become one of the aims of the treatment of bipolar disorder. However, scant attention has been given to family functioning, even though it has a role in the illness outcome and is affected by the disorder. The aims of this study were to compare family functioning reported by euthymic patients with bipolar disorder and healthy controls; explore the level of congruence in the perception of family environment between patients with bipolar disorder and their relatives; and analyse the relationship between clinical variables and family functioning. The sample comprised 82 adult euthymic subjects with bipolar disorder, 82 family caregivers of these patients and 47 healthy controls. Participants completed the Family Environment Scale. Results showed moderate correlations and a mean pattern almost identical between relatives' and patients' reported scores in family functioning subscales. There were significant differences between patients and controls, favourable for the latter, in the subscales cohesion (p<0.005), expressiveness (p=0.002), conflict (p=0.038), intellectual-cultural orientation (p=0.001), active-recreational orientation (p<0.005), and a non-significant trend in organization (p=0.064). Significant associations were found between family environment and clinical variables of severity. These findings contribute to increasing the understanding of family functioning in bipolar disorder and highlight the importance of family work. Highlights: There are significant differences in family functioning between bipolar patients and controls, favourable for the latter. The perception of family functioning between euthymic bipolar patients and their family caregiver is very similar. There are significant associations between poor family functioning and clinical variables of severity. Family functioning should be routinely assessed to guide psychosocial interventions.